Cardiac Anxiety, Depression, And Stress Among The Patients With Myocardial Infarction In A Tertiary Care Center - A Cross-Sectional Study (Applied Biological Research, 2023)
Non-communicable diseases (NCD) are common global public health issues  and among all the NCDs, cardiovascular diseases, Ischemic heart disease, cardiac anxiety, depression, and stress are major health problems. This study was aimed to identify the cardiac anxiety, depression, and stress among the  patients with myocardial infarction (MI). A cross-sectional study was chosen  to measure cardiac anxiety, depression, and stress among the patients with  coronaryartery disease admitted to the coronary care department of a tertiary  care hospital in Bhubaneswar, India. The purposive sampling method  included the study samples. Among the 111 participants, the majority after the  acute event of MI had extremely severe depression (35.1%) and moderate  levels of stress (27.9%). Anterior wall myocardial infarction and inferior wall  myocardial infarction (28.8% each) were more prevalent type of MI among  the participants. The mean value of cardiac anxiety was 39.83 (9.01), 24.38  (7.2) for depression, and 23.93 (8.1) for stress. Hence psychiatric morbidity  assessment is critical among patients with myocardial infarction and should  pan to provide need-based intervention to reduce further mortality and for a  speedy recovery rate.
Keywords: Cardiac anxiety; coronary heart disease; depression; myocardial infarction; stress